Glucocorticoids in vivo induce both insulin hypersecretion and enhanced glucose sensitivity of stimulus-secretion coupling in isolated rat islets - Rafacho, Alex [UNESP]; Marroquí, Laura; Taboga, Sebastião R. [UNESP]; Abrantes, Júlia L. F.; Silveira, Leonardo R.; Boschero, Antonio C.; Carneiro, Everardo M.; Bosqueiro, José Roberto [UNESP]; Nadal, Angel; Quesada, Ivan (The Endocrine Society, 2010)
Although glucocorticoids are widely used as antiinflammatory agents in clinical therapies, they may cause serious side effects that include insulin resistance and hyperinsulinemia. To study the potential functional adaptations of the islet of Langerhans to in vivo glucocorticoid treatment, adult Wistar rats received dexamethasone (DEX) for 5 consecutive days, whereas controls (CTL) received only saline. The analysis of insulin release in freshly isolated islets showed an enhanced secretion in response to glucose in DEX-treated rats. The study of Ca2 2+ signals by fluorescence microscopy also demonstrated a higher response to glucose in islets from DEX-treated animals. However, no differences in Ca2 2+signals were found between both groups with tolbutamide or KCl, indicating that the alterations were probably related to metabolism. Thus, mitochondrial function was explored by monitoring oxidation of nicotinamide dinucleotide phosphate autofluorescence and mitochondrial membrane potential. Both parameters revealed a higher response to glucose in islets from DEX-treated rats. The mRNA and protein content of glucose transporter-2, glucokinase, and pyruvate kinase was similar in both groups, indicating that changes in these proteins were probably not involved in the increased mitochondrial function. Additionally,weexplored the status of Ca2 2+-dependent signaling kinases. Unlike calmodulin kinase II, we found an augmented phosphorylation level of protein kinase Cα as well as an increased response of the phospholipase C/inositol 1,4,5-triphosphate pathway in DEX-treated rats. Finally, an increased number of docked secretory granules were observed in the β-cells of DEX animals using transmission electron microscopy. Thus, these results demonstrate that islets from glucocorticoid-treated rats develop several adaptations that lead to an enhanced stimulus-secretion coupling and secretory capacity. Copyright © 2010 by The Endocrine Society.
Keywords: calcium calmodulin dependent protein kinase II; calcium ion; dexamethasone; glucocorticoid; glucokinase; glucose; glucose transporter 2; inositol 1,4,5 trisphosphate; insulin; messenger RNA; nicotinamide adenine dinucleotide phosphate; phospholipase C; potassium chloride; protein; protein kinase C alpha; pyruvate kinase; sodium chloride; tolbutamide; animal experiment; animal model; autofluorescence; controlled study; drug efficacy; fluorescence microscopy; glucose metabolism; hyperinsulinemia; in vivo study; insulin release; insulin resistance; insulin sensitivity; male; mitochondrial membrane potential; mitochondrion; nonhuman; oxidation; pancreas islet; priority journal; protein content; protein phosphorylation; rat; secretory granule; signal transduction; stimulus response; transmission electron microscopy; treatment response; Adaptation, Biological; Animals; Calcium; Cell Separation; Cells, Cultured; Dexamethasone; Drug Resistance; Drug Synergism; Glucocorticoids; Glucose; Insulin; Insulin Resistance; Islets of Langerhans; Male; Mitochondria; Rats; Rats, Wistar; Signal Transduction; Up-Regulation